Managing multiple, geographically-separated identities, and its effect on employee retention - Unsworth, Kerrie L.; Seivwright, Ami N. (Frontiers in Psychology, 2023)
Extant literature posits that an individual manages their multiple identities by integrating or separating them to varying degrees. We posit that, rather than managing a single set of identities, an individual may engage different identity structures in different contexts. We use the fly-in, fly-out work context, whereby an employee’s home and work are substantially geographically separated, to explore whether different identity structures exist, strategies for managing them, and their effect on employee retention intentions. Analysis of qualitative data from 29 participants collected across three work sites revealed three main strategies that employees adopt to cope with having multiple identity structures: aligning identities; making work identity dominant; and creating a new identity around the working arrangement and discarding all other identities. These strategies interact with the employee’s actual identity structure to influence retention intentions. Implications for retaining employees in such working arrangements are discussed.